A STUDY ON THE IMPACT OF MENTAL HEATH ON ACADEMIC ACHIEVEMENT OF SECONDARY-LEVEL SCHEDULE TRIBE STUDENTS IN UTTAR-DINAJPUR DISTRICT - Paul, Ananta; Acharya, Shnaoli Chakraborty (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Adolescence is the transitional stage of development between childhood and adulthood, representing the period during which a person experiences a variety of biological and emotional changes. During this period, adolescents suffer from various forms of problems, dysfunctions, and conflicts, which ultimately impair normal psychosocial development, aggravating psychosocial dysfunction. The mental health of adolescents is significantly important, as this is the stage where they are developing into adults who should be responsible and committed to adult roles and responsibilities. The aim of the present study is to determine the impact of mental health on the academic achievement of secondary-level Scheduled Tribe students in the Uttar-Dinajpur District. Additionally, it looks at the differences between mentally healthy and unhealthy boys and girls and examines whether these variables are related in mentally healthy and unhealthy students. For this purpose, 200 Scheduled Tribe adolescent students were selected based on inclusion criteria and were divided into two groups: Mentally Healthy (N=100) and Mentally Unhealthy (N=100), according to the GHQ-28. These two groups were further subdivided by gender: Boys (N=50) and Girls (N=50) in both groups. The results indicate that mentally healthy Scheduled Tribe adolescents have higher academic achievement compared to their mentally unhealthy counterparts. When adolescent boys and girls are compared regarding mental health and academic achievement, no significant differences are found.